Socioeconomic status and family functioning influence oral health literacy among adolescents - Roanny Torres Lopes; Érick Tássio Barbosa Neves; Laio da Costa Dutra; Monalisa Cesarino Gomes; Saul Martins Paiva; Mauro Henrique Nogueira Guimarães de Abreu; Fernanda Morais Ferreira; Ana Flávia Granville-Garcia (Universidade de São Paulo, 2020)
ABSTRACT OBJECTIVE Evaluate socio-demographic, family and behavioral factors associated with oral health literacy (OHL) in adolescents. METHODS Cross-sectional study conducted with adolescents aged 15 to 19 years in Campina Grande, Brazil. Parents/guardians answered a questionnaire addressing socio-demographic data. The adolescents answered validated instruments on family cohesion and adaptability (family adaptability and cohesion evaluation scale), drug use (alcohol, smoking and substance involvement screening test), type of dental service used for last appointment and OHL (Brazilian version of the Rapid Estimate of Oral Health Literacy in Dentistry). Two dentists were trained to evaluate OHL (K = 0.87-0.88). Descriptive analysis was performed, followed by Poisson regression analysis (α = 5%). A directed acyclic graph was used to select independent variables in the study. RESULTS The following variables remained associated with better OHL: high mother's schooling level (RR = 1.07; 95%CI: 1.03-1.12), high income (RR = 1.04; 95%CI: 1.01-1.09), white ethnicity/skin color (RR = 1.05; 95%CI: 1.01-1.10), married parents (RR = 1.04; 95%CI: 1.01-1.09), "enmeshed" family cohesion (RR = 1.21; 95%CI: 1.12-1.30), "structured" (RR = 1.06; 95%CI: 1.01-1.12) or "rigid" (RR = 1.11; 95%CI: 1.04-1.19) family adaptability, having more than five residents in the home (RR = 1.07; 95%CI: 1.01-1.14) and having used a private dental service during the last appointment (RR = 1.08; 95%CI: 1.03-1.13). CONCLUSION Family functioning and socio-demographic factors influence the level of oral health literacy among adolescents.